Вплив реабілітаційних заходів на стан працездатності радикально оперованих хворих на рак легенів - Шевченко, Анатолій Іванович; Шевченко, О. І.; Shevchenko, A. I.; Shevchenko, O. I. (My University, 2007)
Стаття присвячена проблемі медичної реабілітації хворих на рак легенів, прооперованих радикально. Медична реабілітація розглядається як важливий засіб відновлення працездатності. Розглянуті такі методи реабілітації: мінімальний травматизм підчас операції, профілактика розвитку плевральних зрощень, комплекс фізичних вправ і дихальна гімнастика. The article is devoted the problem of medical rehabilitation of patients the cancer of lights, operated radically. A medical rehabilitation is examined as an important mean of renewal of ability to work. The followings methods of rehabilitation are considered: a minimum traumatism is operations, prophylaxis of development of unions of pleurae, complex of physical exercises and respiratory gymnastics in time.
Influence of measures of rehabilitations on the state of capacity radically prooperirovanykh of patients by cancer of lights
Keywords: рак легенів; торакотомія; медична реабілітація; функціональні можливості легенів; cancer of lights; torakotomiya; medical rehabilitation; functional possibilities of lights